2010
DOI: 10.2967/jnumed.110.078550
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Noninvasive Serial Assessment of Acute Renal Allograft Rejection by 18F-FDG PET to Monitor Treatment Efficiency

Abstract: We propose 18 F-FDG PET as a method to monitor acute rejection of allogeneic renal transplants in a rat model. Methods: Allogeneically transplanted (aTX) rats (binephrectomized Lewisbrown Norway to Lewis) served as the renal transplant model. aTX rats treated with cyclosporine A (CSA) served as a therapy monitoring group. Healthy control rats, rats with acute CSA nephrotoxicity, rats with acute tubular necrosis, syngeneically transplanted (sTX) rats, and aTX rats treated with CSA since postoperative day 0 serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 37 publications
(52 reference statements)
2
35
0
Order By: Relevance
“…[14][15][16][17][18][19][20][21] Similarly, PET is also now used to detect inflammation 78 that is due to both infectious diseases, such as fever of unknown origin (FUO) and bacteremic foci, [79][80][81] and non-infectious diseases, such as graft rejection in liver and renal transplants. [82][83][84][85] We have recently shown that inflammatory cytokines induce autophagy in cancer-associated fibroblasts, consistent with a shift toward aerobic glycolysis under inflammatory conditions. 7 Interestingly, PET glucose avidity and elevated serum inflammatory markers both correlate with poor prognosis in breast cancers.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 97%
“…[14][15][16][17][18][19][20][21] Similarly, PET is also now used to detect inflammation 78 that is due to both infectious diseases, such as fever of unknown origin (FUO) and bacteremic foci, [79][80][81] and non-infectious diseases, such as graft rejection in liver and renal transplants. [82][83][84][85] We have recently shown that inflammatory cytokines induce autophagy in cancer-associated fibroblasts, consistent with a shift toward aerobic glycolysis under inflammatory conditions. 7 Interestingly, PET glucose avidity and elevated serum inflammatory markers both correlate with poor prognosis in breast cancers.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 97%
“…Moreover, 18 F-FDG PET can be applied for the early evaluation of immunosuppressive treatment response and might assist in the differential diagnosis of AR, ATN, and acute CSA toxicity (8).…”
Section: Discussionmentioning
confidence: 99%
“…Image Acquisition: PET Image acquisition of nonfasting subjects was performed as described before (8,9). In short, T-cell infiltration was calculated from a whole-body acquisition of 20 min at 1 and 2 h after injection of 30 · 10 6 ex vivo 18 F-FDG-labeled human T cells (1-2 MBq of 18 F-FDG) in 300 mL of 0.9% NaCl solution into a tail vein.…”
Section: T-cell Isolation and Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Citation rates show a similar trend, with a surge for all included publications, but a lower rate for publications combining imaging and KTX. Studies focusing on PET/CT for the diagnosis of acute allograft rejection showed significant associations in both acute rat renal allograft models and a clinical study, while the sensitivity remained too low for clinical applications [11][12][13][14].…”
Section: Lessons Learntmentioning
confidence: 99%